A Transient Hermaphroditic Stage in Early Male Gonadal Development in Little Yellow Croaker, Larimichthys polyactis - Xie, Qing-Ping; Li, Bing-Bing; Zhan, Wei; Liu, Feng; Tan, Peng; Wang, Xu; Lou, Bao (Frontiers in Endocrinology, 2021)
Animal taxa show remarkable variability in sexual reproduction, where separate sexes, or gonochorism, is thought to have evolved from hermaphroditism for most cases. Hermaphroditism accounts for 5% in animals, and sequential hermaphroditism has been found in teleost. In this study, we characterized a novel form of the transient hermaphroditic stage in little yellow croaker (Larimichthys polyactis) during early gonadal development. The ovary and testis were indistinguishable from 7 to 40 days post-hatching (dph). Morphological and histological examinations revealed an intersex stage of male gonads between 43 and 80 dph, which consist of germ cells, somatic cells, efferent duct, and early primary oocytes (EPOs). These EPOs in testis degenerate completely by 90 dph through apoptosis yet can be rescued by exogenous 17-β-estradiol. Male germ cells enter the mitotic flourishing stage before meiosis is initiated at 180 dph, and they undergo normal spermatogenesis to produce functional sperms. This transient hermaphroditic stage is male-specific, and the ovary development appears to be normal in females. This developmental pattern is not found in the sister species Larimichthys crocea or any other closely related species. Further examinations of serum hormone levels indicate that the absence of 11-ketotestosterone and elevated levels of 17-β-estradiol delineate the male intersex gonad stage, providing mechanistic insights on this unique phenomenon. Our research is the first report on male-specific transient hermaphroditism and will advance the current understanding of fish reproductive biology. This unique gonadal development pattern can serve as a useful model for studying the evolutionary relationship between hermaphroditism and gonochorism, as well as teleost sex determination and differentiation strategies.